Intervensi Berbasis Self-Efficacy dan Spiritualitas: Implikasi Praktis Pencegahan Quarter Life Crisis di Kalangan Mahasiswa Kesehatan - Toga, Erik; Laili, Roudlotun Nurul; Nashir, Muhammad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: This study aims to identify the relationship between Self-Efficacy, spirituality, and Quarter Life Crisis (QLC) among final-year health students at STIKES Banyuwangi. Methods: A quantitative approach with a cross-sectional correlational design was employed. The study involved 43 final-year students experiencing QLC from a population of 79. Data were collected using the General Self-Efficacy Scale, Spiritual Well-Being Scale, and a QLC questionnaire, then analyzed using Rank Spearman correlation. Results: Most students (60.5%) managed QLC at a